Direitos humanos como modernos Éndoxa: no rastro de Enrico Berti - Figueira, Demócrito de Oliveira (2018)
The present work has as its core theme the debate on the fundamentals of human rights, as delimited by the possibility of defining it as modern Aristotelic éndoxa. Thus, its central question is formulated as following: do the Aristotelic éndoxa present an epistemological value for defining human rights? Within its aim, this work seeks to analyze: (i) what are the éndoxa for Aristotle and their place within the system of Aristotelian sciences; (ii) the current debate on human rights, examining its principles based on Norberto Bobbio and how does Enrico Berti’s approach participate in this debate; (iii) the definition of human rights as modern éndoxa and their reach and limits considering the theses by Herrera Flores and Costas Douzinas. Its central hypothesis is that of compatibility of human rights as modern éndoxa. Methodologically, this approach was qualitative and developed by means of bibliographic research, also conducting procedures under a historical comparative method. Regarding its conclusive aspect, we found inconsistencies of the classical human rights theory and the possibilities for a critical theory for the fact, combined with the Aristotelic paradigm.